Fatty Acids Constitution of Selected Franchised Snacks in Nigeria - Uthman-Akinhanmi, Yewande O.; Yangomodou, O. D.; Solana, O. I.; Lawal, A. O. (NIU Journal of Humanities; Vol 6 No 3 (2021): KIU Journal of Humanities, Vol. 6 No. 3, September 2021, 2021)
There has been an increase in the frequency of consumption of fast foods in Nigeria. This study aimed to investigate the fatty acid composition of franchised snacks available in south-western Nigeria. Five non-meat-based and five meat-based fast foods were selected from ten fast food outlets from South-west Nigeria using systematic random sampling. The samples were analyzed for fatty acids composition using gas chromatography-mass spectrometry. Saturated fatty acids (SFA) ranged from 0.72 in popcorn to 11.44 g/100g in doughnut, n-3 unsaturated fatty acid [0.30 doughnut to 2.62 g/100g in meat pie], n-6 unsaturated fatty acids[0.55 in doughnut to 2.03 g/100g beef roll], n-9 unsaturated fatty acids [0.21sausage roll to 6.59 g/100g beef roll] and Trans fatty acids (TFAs) content [0.29popcorn to 11.78 g/100g sausage roll]. However, elaidic acid was abundant in almost all non-meat-based snacks (406.60 to 1146.33 mg) and vaccenic acid in almost all meat based samples (324.03 to 2307.60 mg) except in meat pie. The study established that snacks consumed in south-western Nigeria are abundant in SFA, TFA and unsaturated fatty acids and this information will aid in making informed choice during selection of snacks by consumers. Keywords: Fat content, fast foods, lipids, saturated fats, pastries.